Association between occupation type and development of type 2 diabetes: A population-based Panasonic cohort study 3 - Habu, Momoko; Okada, Hiroshi; Hamaguchi, Masahide; Kurogi, Kazushiro; Murata, Hiroaki; Ito, Masato; Fukui, Michiaki (Frontiers in Public Health, 2023)
Background: Due to a lack of investigation on the association between the type of occupation and the development of type 2 diabetes among Japanese individuals, we aimed to assess this association in 98,935 Japanese individuals. Methods: This long-term retrospective cohort study included participants selected from medical health checkup programs conducted at the Panasonic Corporation, Osaka, Japan, from 2008 to 2018. Cox regression analyses were used to evaluate the association between occupation type and the incidence of type 2 diabetes. Results: From 2008 to 2018, 5,008 participants developed type 2 diabetes. The proportion of never smokers, those with slow eating speeds, and those working with a flextime system was higher in men with technical jobs than in salespersons, manufacturers, and office workers (p < 0.0001). Cox regression analyses revealed that occupation type was associated with an increased probability of type 2 diabetes development in men but not in women. Multivariate analyses showed that the hazard ratios were 1.15 (95% confidence interval (CI), 1.05–1.26), 1.20 (95% CI, 1.10–1.30), and 1.11 (95% CI, 1.02–1.21) in men working as salespersons, manufacturers, and office workers, respectively (reference group: men with technical jobs). On the other hand, the occupation type was not associated with the development of type 2 diabetes in women. Conclusions: This study demonstrated that occupation type might be an independent factor in the development of type 2 diabetes in Japanese men.